Analisis Dan Implementasi Akses Point Berbasis Mikrotik Menggunakan Hub Dengan Metode PPDIOO - rahmat rahmat azis; Sri Dianing Asri (JSAI (Journal Scientific and Applied Informatics), 2025)
This research discusses the analysis and implementation of Mikrotik-based access points using hubs as a connection medium, with the PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) methodology approach. PPDIOO was chosen because it is able to provide a systematic, efficient work structure, and can be evaluated in stages using success indicators (KPIs). Tests were conducted at the Operate and Optimize stages with a focus on throughput (Tx/Rx) metrics, average data transmission speed, and packet loss. The test results show a current Tx throughput value of 13.2 Gbps, a 10-second average of 12.9 Gbps, and a total average of 13.7 Gbps, with no packet loss (0 packet loss). Converting these results into percentages shows success above 90% across all indicators, with connection reliability reaching 100%. These findings prove that the PPDIOO method is effective in designing and managing a stable, efficient, and high-performance access point network.